Penegakan Sanksi Disiplin Aparatur Sipil Negara Yang Tidak Menjalankan Tugas - Laim, Aderisal; Nendissa, Renny Heronia; Holle, Eric Stenly (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2023)
The need for strict disciplinary sanctions to be applied to state civil servants who do not carry out their duties because many state civil servants in the Aru islands district do not carry out their duties properly. The aim of the research is to determine and analyze forms of enforcement of disciplinary sanctions for State Civil Apparatus who do not carry out their duties and to analyze the legal consequences. This study uses a normative research type using a statutory approach and a conceptual approach. The legal materials used are primary and secondary legal materials. Legal materials were obtained from literature studies and were processed and analyzed qualitatively. The results of the this study indicate that enforcing the discipline of the state civil apparatus is an effort to foster state civil servants who are not carrying out their duties. With the goverment’s commitment to provide the best service to the community. And the formation of discipline which can be carried out in two ways, namely through the application of strict disciplinary measures.